2019
DOI: 10.3390/foods8120680
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of β-Glucan, Phenolic Acids, and Proteins as Functional Phytonutrients of Hull-Less Barley Grain

Abstract: Two hull-less barley varieties were roller-milled, and breaks (B) and reduction flours (C), shorts, and bran were collected. Shorts, which mainly originate from endosperm cells with a smaller amount of the outer layers, had the largest yield (48.87-51.54%). Ash (0.82-3.10%) and protein (9.95-14.8%) increased from flours toward shorts and bran, while starch decreased (82.31-48.69%). In contrast to clear distribution differences in protein content (bran > shorts > C > B), albumins/globulins content was lowest in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 49 publications
1
12
2
Order By: Relevance
“…The highest amount of TPC in bran fraction was found in TIOS and HLES (6.05 and 5.98 mg GAE/g) and the lowest in THMI (3.46 mg GAE/g), while the mean value among all barley cultivars was 4.63 mg GAE/g. Similarly, Šimic et al [29] reported that TPC of a hull-less cultivar was greatest in the bran in comparison to the refined flour; however, they found lower values for bran than those from our study. On the other hand, Moza and Gujral [30] reported similar values of TPC in the bran fraction in hull-less cultivars (3.67-4.44 mg FAE/g).…”
Section: Phenolic Contents and Antioxidant Activity Of Barley Pearlincontrasting
confidence: 59%
See 1 more Smart Citation
“…The highest amount of TPC in bran fraction was found in TIOS and HLES (6.05 and 5.98 mg GAE/g) and the lowest in THMI (3.46 mg GAE/g), while the mean value among all barley cultivars was 4.63 mg GAE/g. Similarly, Šimic et al [29] reported that TPC of a hull-less cultivar was greatest in the bran in comparison to the refined flour; however, they found lower values for bran than those from our study. On the other hand, Moza and Gujral [30] reported similar values of TPC in the bran fraction in hull-less cultivars (3.67-4.44 mg FAE/g).…”
Section: Phenolic Contents and Antioxidant Activity Of Barley Pearlincontrasting
confidence: 59%
“…Similarly, Izydorczyk et al [25] also found that barley pearling by-products were contained high levels in arabinoxylans, protein and ash and low amounts of β-glucans and starch. On the contrary, in two hull-less and two waxy barleys, the greatest β-glucan content was determined in the bran, according to Šimic et al [29].…”
Section: Chemical Characterization Of Barley Pearling Fractionsmentioning
confidence: 99%
“…The high β-glucan content in barley grains makes it an attractive ingredient for development of novel functional flours [4]. In addition to β-glucan, barley contains some other bioactive compounds (phenolic compounds, tocols and sterols) with beneficial effects that are currently under extensive investigation [5]. Therefore, there is a large potential to include barley flour partially or as a whole grain in a wide range of cereal-based food products as an alternative to commonly used cereals (wheat, rice, maize and oat).…”
Section: Introductionmentioning
confidence: 99%
“…Arabinoxylans Fermentation [102][103][104] Ultrasonic/microwave [105,106] Enzymatic treatment [107][108][109][110] Milling fractions [111][112][113] Alkaline treatment [114][115][116][117] Nixtamalization [118] Starch removal [119] Extrusion [80,86,89,120] Subcritical water treatment [119,121] β-glucans Ultrasound [122] Roller-milling/pearling [123] Milling [124][125][126] Fermentation [127,128] Enzymatic treatment [129,130] Extrusion [131][132][133][134] Subcritical water treatment [119,135,136]…”
Section: Compound Techniques Referencesmentioning
confidence: 99%